Antibacterial Activity of Plant Extract: the Role of Lemongrass and Chili Extracts, a Bacteriocin from Bacillus velezensis BUU004, and Their Combination to Control Staphylococcus aureus in Dried, Seasoned and Crushed Squid - Soodsawaeng, Pornpimon; Boonthai, Traimat; Vuthiphandchai, Verapong; Nimrat, Subuntith (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023DO - 10.14456/nujst.2023.10, 2022)
Staphylococcus aureus is the leading cause of foodborne bacterial diseases worldwide, and exists in a wide variety of food products in Thailand, particularly dried seafood products. This study evaluated the inhibitory potential against S. aureus of mixed extracts of lemongrass and hot chili (MLC), bacteriocin, which is produced by Bacillus velezensis BUU004, and their combination, and their effects on physicochemical quality of dried, seasoned, and crushed squids. Dried squid samples were inoculated with S. aureus suspension and then divided into 4 treatments: addition of 1) distilled water (control), 2) a partially-purified solution containing bacteriocin from B . velezensis BUU004 (PPS-BV; 800 AU/mL), 3) an MLC (160 mg/mL), and 4) a combination of the PPS-BV and MLC. Squid samples were maintained at 2 storage temperatures: either at 4°C or room temperature (approximately 25°C) for 28 days. Two administration regimes of the tested additives were applied: a single addition at the onset of the experiment, and a 14-day addition at 14 and 28 days of storage. Strong anti-staphylococcal activity was observed in the dried squids treated with MLC, and a combination of the PPS-BV and MLC during 28-day storage at both conditions, in particular when the 14-day addition was applied. In contrast, the PPS-BV was ineffective against S. aureus in the dried squid samples. The MLC and the combination had bactericidal potency by destroying the bacterial cell walls and cell lysis. Supplementation of the MLC caused a significant reduction ( p <0.05) in pH simultaneously with a significant increase ( p <0.05) in the water activity of the dried squid during storage. This study suggests a potential use of MLC as a biopreservative for controlling the growth of S . aureus in dried seafood products. Keywords: Food safety, Seafood, Bacillus , Bacteriocin, Biopreservation